Recent progress in the racemic and enantioselective synthesis of monofluoroalkene-based dipeptide isosteres - Drouin, Myriam; Paquin, Jean-François (Beilstein Journal of Organic Chemistry, 2017)
Monofluoroalkenes are fluorinated motifs that can be used to replace amide bonds. In order to be incorporated into peptides, it is normally necessary to first synthesize a dipeptide where the amide bond has been replaced with a monofluoroalkene. In that context, this review will present the racemic and enantioselective synthesis of monofluoroalkene-based dipeptide isosteres described since 2007. Some applications of those compounds will also be presented.
Keywords: dipeptide isosteres; monofluoroalkene-based amide bonds; monofluoroalkenes; peptides; synthesis

(untitled) - Newman, D. J.; Cragg, G. M. (J. Nat. Prod., 2012)

(untitled) - Craik, D. J.; Fairlie, D. P.; Liras, S.; Price, D. (Chem. Biol. Drug Des., 2013)

(untitled) - Vlieghe, P.; Lisowski, V.; Martinez, J.; Khrestchatisky, M. (Drug Discovery Today, 2010)

(untitled) - Choudhary, A.; Raines, R. T. (ChemBioChem, 2011)

Fluorine in Medicinal Chemistry and Chemical Biology - Taguchi, T.; Yanai, H. (Fluorinated Moieties for Replacement of Amide and Peptide Bonds, 2009)

(untitled) - Angell, Y. L.; Burgess, K. (Chem. Soc. Rev., 2007)

(untitled) - Wipf, P.; Henninger, T. C.; Geib, S. J. (J. Org. Chem., 1998)

(untitled) - Abraham, R. J.; Ellison, S. L. R.; Schonholzer, P.; Thomas, W. A. (Tetrahedron, 1986)

(untitled) - Champagne, P. A.; Desroches, J.; Paquin, J.-F. (Synthesis, 2015)

(untitled) - O’Hagan, D.; Rzepa, H. S. (Chem. Commun., 1997)

(untitled) - Howard, J. A. K.; Hoy, V. J.; O’Hagan, D.; Smith, T. G. (Tetrahedron, 1996)

(untitled) - Urban, J. J.; Tillman, B. G.; Cronin, W. A. (J. Phys. Chem. A, 2006)

(untitled) - Joseph, A. P.; Srinivasan, N.; de Brevern, A. G. (Amino Acids, 2012)

(untitled) - Ramachandra, G. N.; Sasisekharan, V. (Adv. Protein Chem., 1968)

(untitled) - Ramachandra, G. N.; Mitra, A. K. (J. Mol. Biol., 1976)

(untitled) - van Steenis, J. H.; van der Gen, A. (J. Chem. Soc., Perkin Trans. 1, 2002)

(untitled) - Zajc, B.; Kumar, R. (Synthesis, 2010)

(untitled) - Landelle, G.; Bergeron, M.; Turcotte-Savard, M.-O.; Paquin, J.-F. (Chem. Soc. Rev., 2011)

(untitled) - Yanai, H.; Taguchi, T. (Eur. J. Org. Chem., 2011)

(untitled) - Hara, S. (Top. Curr. Chem., 2012)

(untitled) - Pfund, E.; Lequeux, T.; Gueyrard, D. (Synthesis, 2015)

(untitled) - Champagne, P. A.; Desroches, J.; Hamel, J.-D.; Vandamme, M.; Paquin, J.-F. (Chem. Rev., 2015)

(untitled) - Sano, S.; Kuroda, Y.; Saito, K.; Ose, Y.; Nagao, Y. (Tetrahedron, 2006)

(untitled) - Calata, C.; Pfund, E.; Lequeux, T. (J. Org. Chem., 2009)

(untitled) - Calata, C.; Pfund, E.; Lequeux, T. (Tetrahedron, 2011)

(untitled) - Yanai, H.; Okada, H.; Sato, A.; Okada, M.; Taguchi, T. (Tetrahedron Lett., 2011)

(untitled) - Sato, A.; Yanai, H.; Suzuki, D.; Okada, M.; Taguchi, T. (Tetrahedron Lett., 2015)

(untitled) - Nihei, T.; Nishi, Y.; Ikeda, N.; Yokotani, S.; Ishihara, T.; Arimitsu, S.; Konno, T. (Synthesis, 2016)

(untitled) - Boros, L. G.; De Corte, B.; Gimi, R. H.; Welch, J. T.; Wu, Y.; Handschumacher, R. E. (Tetrahedron Lett., 1994)

(untitled) - Welch, J. T.; Lin, J. (Tetrahedron, 1996)

(untitled) - Van der Veken, P.; Kertèsz, I.; Senten, K.; Haemers, A.; Augustyns, K. (Tetrahedron Lett., 2003)

(untitled) - Sano, S.; Matsumoto, T.; Nakao, M. (Tetrahedron Lett., 2014)

(untitled) - Sano, S.; Matsumoto, T.; Nanataki, H.; Tempaku, S.; Nakao, M. (Tetrahedron Lett., 2014)

(untitled) - Pierry, C.; Couve-Bonnaire, S.; Guilhaudis, L.; Neveu, C.; Marotte, A.; Lefranc, B.; Cahard, D.; Ségalas-Milazzo, I.; Leprince, J.; Pannecoucke, X. (ChemBioChem, 2013)

(untitled) - Guérin, D.; Dez, I.; Gaumont, A.-C.; Pannecoucke, X.; Couve-Bonnaire, S. (Org. Lett., 2016)

(untitled) - Nadon, J.-F.; Rochon, K.; Grastilleur, S.; Langlois, G.; Hà Dao, T. T.; Blais, V.; Guérin, B.; Gendron, L.; Dory, Y. L. (ACS Chem. Neurosci., 2017)

(untitled) - Narumi, T.; Niida, A.; Tomita, K.; Oishi, S.; Otaka, A.; Ohno, H.; Fujii, N. (Chem. Commun., 2006)

(untitled) - Pierry, C.; Zoute, L.; Jubault, P.; Pfund, E.; Lequeux, T.; Cahard, D.; Couve-Bonnaire, S.; Pannecoucke, X. (Tetrahedron Lett., 2009)

(untitled) - Pierry, C.; Cahard, D.; Couve-Bonnaire, S.; Pannecoucke, X. (Org. Biomol. Chem., 2011)

(untitled) - Yamaki, Y.; Shigenaga, A.; Tomita, K.; Narumi, T.; Fujii, N.; Otaka, A. (J. Org. Chem., 2009)

(untitled) - Karad, S. N.; Pal, M.; Crowley, R. S.; Prisinzano, T. E.; Altman, R. A. (ChemMedChem, 2017)

(untitled) - Sommer, H.; Fürstner, A. (Chem. – Eur. J., 2017)

(untitled) - Jakobsche, C. E.; Peris, G.; Miller, S. J. (Angew. Chem., Int. Ed., 2008)

(untitled) - Okada, M.; Nakamura, Y.; Saito, A.; Sato, A.; Horikawa, H.; Taguchi, T. (Tetrahedron Lett., 2002)

(untitled) - Nakumara, Y.; Okada, M.; Sato, A.; Horikawa, H.; Koura, M.; Saito, A.; Taguchi, T. (Tetrahedron, 2005)

(untitled) - Watanabe, D.; Koura, M.; Saito, A.; Yanai, H.; Nakamura, Y.; Okada, M.; Sato, A.; Taguchi, T. (J. Fluorine Chem., 2011)

(untitled) - Yamaki, Y.; Shigenaga, A.; Li, J.; Shimohigashi, Y.; Otaka, A. (J. Org. Chem., 2009)

(untitled) - Narumi, T.; Tomita, K.; Inokuchi, E.; Kobayashi, K.; Oishi, S.; Ohno, H.; Fujii, N. (Tetrahedron, 2008)

(untitled) - Oishi, S.; Kamitani, H.; Kodera, Y.; Watanabe, K.; Kobayashi, K.; Narumi, T.; Tomita, K.; Ohno, H.; Naito, T.; Kodama, E.; Matsuoka, M.; Fujii, N. (Org. Biomol. Chem., 2009)

(untitled) - Narumi, T.; Hayashi, R.; Tomita, K.; Kobayashi, K.; Tanahara, N.; Ohno, H.; Naito, T.; Kodama, E.; Matsuoka, M.; Oishi, S.; Fujii, N. (Org. Biomol. Chem., 2010)

(untitled) - Niida, A.; Tomita, K.; Mizumoto, M.; Tanigaki, H.; Terada, T.; Oishi, S.; Otaka, A.; Inui, K.-i.; Fujii, N. (Org. Lett., 2006)

(untitled) - Chang, W.; Mosley, R. T.; Bansal, S.; Keilman, M.; Lam, A. M.; Furman, P. A.; Otto, M. J.; Sofia, M. J. (Bioorg. Med. Chem. Lett., 2012)

(untitled) - Dutheuil, G.; Pierry, C.; Villiers, E.; Couve-Bonnaire, S.; Pannecoucke, X. (New J. Chem., 2013)

(untitled) - Villiers, E.; Couve-Bonnaire, S.; Cahard, D.; Pannecoucke, X. (Tetrahedron, 2015)

(untitled) - Tomita, K.; Narumi, T.; Niida, A.; Oishi, S.; Ohno, H.; Fujii, N. (Biopolymers, 2007)